REPURCHASE INTENTION OF WATCH PRODUCTS AT SHOPEE MARKETPLACE IN BATAM CITY THROUGH CUSTOMER BRAND ENGAGEMENT - Aulia, Rizni; Asri, Dhita Hafizaha; Andelson, Jeffrey (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to explore the impact of perceived perceivable behavior control, customer satisfaction, trust, e-WOM, and customer brand engagement on repurchase intention at marketplace in the city of Batam, Indonesia. The research method uses a qualitative approach by collecting primary data through questionnaires, with a target sample of 200 respondents. Data analysis was carried out using the Smart PLS method. The results of the study show that perceived perceived behavioral control has a significant impact on repurchase intention. Meanwhile, customer satisfaction does not have a significant impact on repurchase intention, but trust and E-WOM show a significant influence on repurchase intention, especially with the mediation of customer brand engagement.